Upaya Memantapkan Pasangan Calon Pengantin Melalui Program Belajar Rahasia Nikah (Berkah) Perspektif Maqasid Shari’ah (Studi Kasus Kantor Urusan Agama Kecamatan Sawahan Surabaya) - Liana, Pipit; Panjalu, Gandhung Fajar (MAQASID, 2020)
ABSTRACTBased on the reality that is happening now. Divorce in some cities has increased, especially in Surabaya city. Therefore, the Office of Religious Affairs (KUA) Sawahan runs a secret marriage learning program (BERKAH) with the aim of stabilizing the bride and groom. The program is instructed directly from KUA center to KUA sub-districts with class A status and this research aims to provide supplies to bride and groom couples.This type of research is included in the field research, namely research based on the results of observations and interviews with the head of the KUA Sawahan District regarding the BERKAH program. The researcher collected data directly and interviewed the parties concerned at the KUA Sawahan District, Surabaya City. After the data is collected, the author analyzed using a qualitative method.The results of the research stated that the program was an attempt to provide provisions for the bride and groom. In order for the bride and groom to be more stable in running the household. From the perspective of Maqa>s{id Shari>’ah, the program is very closely related to maintaining religion, maintaining the soul, maintaining reason, guarding offspring and protecting property.Keywords: Consolidation of Brides, BERKAH Program, Maqa>s{id Shari>’ah.